331 AN UNUSUAL CASE OF PERIPHERAL LYMPHADENOPATHY. Issue 1 (1st January 2007) - Sumrall, A.; Warren, R.
Abstract : Peripheral lymphadenopathy is often a benign finding in a healthy individual but may represent an underlying infection, neoplasm, or autoimmune process. The differential of such a lesion is vast but can be narrowed based on the presence of localized or generalized lymphadenopathy on physical examination. A previously healthy 37-year-old male presented to clinic in April 2001 complaining of a painless lump in his left inguinal region of 6 months' duration. Physical examination revealed a soft nonmatted 3 cm mass in the left inguinal canal. History was unremarkable. Laboratory examination revealed a normal CBC and chemistry panel. A CT scan of the chest, abdomen, and pelvis showed a lytic lesion of the left pubic ramus, measuring 2.6 × 2.7 cm. He promptly underwent lymph node biopsy, which showed angiofollicular lymphoid hyperplasia, which was consistent with Castleman's disease, hyaline-vascular type. Further laboratory investigation by serum protein electrophoresis showed a small monoclonal IgG gammopathy with normal uninvolved immunoglobulins. Bone biopsy of the lytic lesion in the pelvis revealed a plasmacytoma for which radiation therapy was initiated. After radiation was complete, the monoclonal gammopathy resolved. A bone marrow aspirate was unremarkable. The patient was followed every 6 months by hematology. Repeat bone marrow aspiration in October 2001 remained unremarkable. He was doing well until December 2005 when repeat CT scan showed enlargement of the left iliac lesion. Laboratory examination showed recurrence of monoclonal gammopathy and hypercalcemia. Although bone marrow aspirate in January 2006 remained unremarkable, it was determined that the patient had developed multiple myeloma. He was referred to the University of Mississippi Medical Center in February 2006 for bone marrow transplant. This case is the first reported occurrence of concomitant Castleman's disease and multiple myeloma. It appears that the pathophysiology involves similar biochemical markers as HHV-8 and IL-6 have been described in association with multiple myeloma and multicentric CD. This case is unusual in that the patient has unicentric CD, which is usually not associated with HHV-8, but has multiple myeloma which can be associated with HHV-8. This suggests that IL-6 is more involved than initially believed. More research into these biochemical markers is needed to further understand these conditions.